Water Retention Curve of Soil at Simpang Meo Region South Sumatra - Purnamawati; Gumay, Herdian; Gofar, Nurly (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Steep slopes are typically formed on residual soil with deep groundwater levels; hence, the slopes are in the unsaturated zone. Therefore, in analyzing the stability of steep slopes, it is necessary to consider the properties of unsaturated soil. The main property of unsaturated soil is the Water Retention Curve (SWCC), which describes the relationship between matric suction and soil moisture content. Many methods are available to determine the SWCC of a soil, such as laboratory and field tests, as well as empirical equations. Laboratory testing is considered the best method for determining the SWCC. However, the laboratory work involved in the determination of SWCC is tedious; thus, several models have been developed by researchers to obtain SWCC. This study compares SWCC obtained based on the results of laboratory testing using an Osmotic Tensiometer assisted by soil shrinkage measurements using a 3-D scanner, and the SWCC obtained using the empirical equation proposed by Zapata for plastic soil based on the percentage of particles passing the No. 200 sieve and the soil plasticity index. The soil samples were retrieved from a location in the Simpang Meo region in South Sumatra. Air entry value for the SWCC was obtained both graphically and deterministically. Both methods resulted in a lower air entry value (AEV) for the Zapata equation as compared to the osmotic tensiometer test. A lower AEV indicates that lower suction is required for water to enter the soil pores. Therefore, analysis of rainfall infiltration and slope stability using SWCC curves estimated from the Zapata equation could result in later saturation of soil, hence a slightly higher factor of safety